STRATEGI MENUMBUHKAN MINAT KEWIRAUSAHAAN SANTRI SEBAGAI LANGKAH MENCETAK SANTRIPRENEUR - Suyanto Suyanto; Wisnu Untoro; Asri Laksmi Riani (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2018)
As an Islamic educational institution with a dormitory system, a kiyai as a central figure and a mosque as the central point that animates the doctrine of independence, self-help, self-help, entrepreneurship, should be able to support many people are the motivations that are often conveyed in many occasions so that the intention or the motivation of being an entrepreneur is carried away in such a way that post life passes Pondok Modern Darussalam Gontor (PMDG).. How does the strategy to grow the entrepreneurial interest of santri is instilled in the form of assignments and education indirectly. This study aims to produce studies and the discovery of strategies of forms of assignment and education that shape the behavior of entrepreneurs that foster the entrepreneurial interest of santri. The method in this research is by using quantitative research method. The location of this research is at Pondok Modern Darussalam Gontor Putra in Ponorogo and Pondok Modern Darussalam Gontor Putri in Mantingan, Ngawi. Primary data in this research is santri Pondok Modern Darussalam Gontor Putra or Putri who once manage the cottage business unit. Secondary data in this research are santri data and profile of Pondok Modern Darussalam Gontor. Based on the data in this study was analyzed quantitatively through the multivariate method of Structural Equation Model (SEM) technique using combining Factor Analysis and Path Analysis. The result of data analysis stated that the short-term intention of santri to become entrepreneur is influenced by attitude variable, subjective norm, and perceived behavior control.